2020
DOI: 10.3390/v12090918
|View full text |Cite
|
Sign up to set email alerts
|

X69R Is a Non-Essential Gene That, When Deleted from African Swine Fever, Does Not Affect Virulence in Swine

Abstract: African swine fever virus (ASFV) is currently causing devastating outbreaks in Asia and Europe, and the ASFV strain Georgia (ASFV-G) is responsible for these outbreaks. ASFV-G is highly virulent and continues to be maintained in these outbreak areas, apparently without suffering significant genomic or phenotypic changes. When comparing the genome of ASFV-G to other isolates, a thus-far uncharacterized gene, X69R, is highly conserved and, interestingly, is similar to another ASFV uncharacterized gene, J64R. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…There is no information regarding the possible biological function(s) of the I8L gene, including virus replication. Mounting evidence suggests an increasing number of virus genes are not essential for ASFV replication [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 17 , 27 ]. It is possible that I8L gene function is duplicated by a different ASFV gene that is yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no information regarding the possible biological function(s) of the I8L gene, including virus replication. Mounting evidence suggests an increasing number of virus genes are not essential for ASFV replication [ 4 , 5 , 7 , 8 , 9 , 10 , 11 , 17 , 27 ]. It is possible that I8L gene function is duplicated by a different ASFV gene that is yet to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, identifying viral proteins that are important for in vitro and in vivo virus replication, and importantly in virus virulence in swine, is essential for the development of novel countermeasures to control the disease. Just a small number of genes have been successfully deleted from the ASFV genome, producing novel recombinant viruses (e.g., 9GL, UK, TK, MGF, NL, CD2, Lectin, DP148R, L83L, I177L, C962R, X69R) [ 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] with a subset of deleted genes determined to be essential for virus replication (e.g. : EP152R, p30, p54, and p72) [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the deletion of the 285L or X69R gene from the genome of a virulent ASFV strain virus does not affect virus replication in PAMs and that of X69R does not affect virus virulence (Hübner et al., 2019; Ramirez‐Medina et al., 2020). Similarly, these two genes were deleted from the genome of ASFV‐P121.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, en términos de mortalidad, Asia representa el 82 %, con un total de 6,733,791 cerdos domésticos muertos. La elevada virulencia de cepas asociadas con el genotipo II ha sido evidenciada experimentalmente en cerdos domésticos y jabalíes, se ha identificado hasta el 100 % de mortalidad de los animales infectados en un lapso no mayor a los 7 a 10 días posteriores a la infección (165)(166)(167)(168) .…”
Section: Peste Porcina Africanaunclassified